Targeting Strategies for the Combination Treatment of Cancer Using Drug Delivery Systems - Kydd, Janel (Pharmaceutics, 2017)
Cancer cells have characteristics of acquired and intrinsic resistances to chemotherapy treatment—due to the hostile tumor microenvironment—that create a significant challenge for effective therapeutic regimens. Multidrug resistance, collateral toxicity to normal cells, and detrimental systemic side effects present significant obstacles, necessitating alternative and safer treatment strategies. Traditional administration of chemotherapeutics has demonstrated minimal success due to the non-specificity of action, uptake and rapid clearance by the immune system, and subsequent metabolic alteration and poor tumor penetration. Nanomedicine can provide a more effective approach to targeting cancer by focusing on the vascular, tissue, and cellular characteristics that are unique to solid tumors. Targeted methods of treatment using nanoparticles can decrease the likelihood of resistant clonal populations of cancerous cells. Dual encapsulation of chemotherapeutic drug allows simultaneous targeting of more than one characteristic of the tumor. Several first-generation, non-targeted nanomedicines have received clinical approval starting with Doxil(®) in 1995. However, more than two decades later, second-generation or targeted nanomedicines have yet to be approved for treatment despite promising results in pre-clinical studies. This review highlights recent studies using targeted nanoparticles for cancer treatment focusing on approaches that target either the tumor vasculature (referred to as ‘vascular targeting’), the tumor microenvironment (‘tissue targeting’) or the individual cancer cells (‘cellular targeting’). Recent studies combining these different targeting methods are also discussed in this review. Finally, this review summarizes some of the reasons for the lack of clinical success in the field of targeted nanomedicines.